Marketing and innovation processes in SMEs in a locality of Bogotá - Rocío Peña (GEON Journal (Management, Organizations and Business), 2015)
The Uniagustiniana aware of its impact and ability to contribute to organizational base would provide from a rigorous and systematic study of building the information on marketing and innovation processes that have the companies. It seeks to answer the question What are the processes of marketing and innovation of SMEs in the sector adjacent to the University? in order to propose marketing strategies for business strengthening SMEs in the sector. This is a study of two phases, one documentary and other fieldwork with a mixed design of exploratory and descriptive, with the secondary source information from the local mayor, Chamber of Commerce of Bogota, as primary sources and interviews entrepreneurs. As partial results of the pilot are sparse business and marketing strategies, the latter are recurring on the needs of small businesses, projected plans to improve their situation have to do with the exploration of new markets and product innovation.
Keywords: Innovation; Marketing; SMEs; Strategies; Needs